History of development of criminal responsibility for commercial bribery - Maimakova, A.B.; Amanzholova, B.A.; Kudryavtseva, A.V. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article is devoted to the history of the formation of Kazakhstan legislation on criminal liability for commercial bribery. In connection with the emergence of enterprises and organizations with non-state forms of ownership, the question arose of protecting their interests and, therefore, the criminal responsibility of persons performing managerial functions in them, as well as delimiting their responsibility from those responsible for official crimes, including bribery. Bribery of executives or employees of commercial banks, large economic entities with a monopoly position in the market and based on private property, began to pose a serious danger to the normal functioning of market relations in the economy. The ongoing economic reforms demanded a new criminal law regulation of social relations that characterize commercial bribery to commercial and other organizations. Based on the generalization of the theory of criminal law, it was concluded that when committing acts included in Chapter 9 of the Criminal Code of RK, the harm is caused to the interests of a commercial or non-profit organization, and not to the service. In this regard, it was proposed to change the title of Chapter 9 of the Criminal Code of the Republic of Kazakhstan.
Коммерциялық параға сатып алу үшін қылмыстық жауапкершіліктің даму тарихы
История развития уголовной ответственности за коммерческий подкуп
Keywords: commercial bribery; criminal responsibility; official; commercial and other organizations; interests of the service